2017
DOI: 10.1097/qai.0000000000001164
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: PrEP Uptake, Adherence, and Discontinuation Among California YMSM Using Geosocial Networking Applications

Abstract: We investigated PrEP uptake, adherence, and discontinuation among young app-using MSM in California (N=761). 9.7% of participants had ever used PrEP; 87% of those deemed good candidates for screening (indicated by a CDC risk index score ≥10) were not current or past users. PrEP use was associated with higher income (aOR:4.13; CI:1.87-9.12), receptive condomless anal sex(aOR:3.41; CI:1.71-6.78), HIV-positive sex partners (aOR:2.87; CI:1.53-5.38), popper use (aOR:3.47; CI:1.96-6.13), and recent STI diagnosis (aO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 34 publications
5
91
4
Order By: Relevance
“…For example, in the clinical trial study in Shanghai, actual uptake was only 2.5% compared to 19.1% of participants who said they were willing to use oral PrEP [22]. Therefore Concerns of side effects have been identified as one of the major reasons of not willing to use PrEP among study participants, this was consistent with previous studies among Chinese MSM [26,27] and MSM in other countries [28]. While there are some side effects when first starting the medication, such as nausea and frequent vomiting, they usually abate after two months into the regimen [4,29].…”
Section: Discussionsupporting
confidence: 84%
“…For example, in the clinical trial study in Shanghai, actual uptake was only 2.5% compared to 19.1% of participants who said they were willing to use oral PrEP [22]. Therefore Concerns of side effects have been identified as one of the major reasons of not willing to use PrEP among study participants, this was consistent with previous studies among Chinese MSM [26,27] and MSM in other countries [28]. While there are some side effects when first starting the medication, such as nausea and frequent vomiting, they usually abate after two months into the regimen [4,29].…”
Section: Discussionsupporting
confidence: 84%
“…PrEP among study participants, this was consistent with previous studies among Chinese MSM [36,37] and MSM in other countries [38]. While there are some side effects when first starting the medication, such as nausea and frequent vomiting, they usually abate after two months into the regimen [4,39].…”
Section: Concerns Of Side Effects Have Been Identified As One Of the supporting
confidence: 90%
“…Recent research on reasons for discontinuation (regardless of whether ongoing PrEP is indicated) include cost, loss of insurance, stigma, change in risk perception, and concern about long-term side effects. [8][9][10] In addition, required quarterly follow-up clinic visits and laboratory testing have been considered a potential barrier to longer term persistence in PrEP care. [11][12][13][14][15] Indeed, a recent study conducted in San Francisco, a location with robust PrEP care, found that the most common reason for discontinuation was difficulty attending clinic visits or completing laboratory tests.…”
Section: Introductionmentioning
confidence: 99%